Housing Affordability: Lessons from the United States - Mark Skidmore (New Zealand Government, The Treasury, 2014)
Over the last two decades, New Zealand experienced a threefold increase in housing prices. The largest surge in prices in recent years occurred between 1998 and 2007, a period of housing price growth in many developed economies. Since 2007, housing price growth remained flat until 2011, and then prices once again embarked on an upward trend. However, recent housing price growth has been concentrated in Auckland and Christchurch. The purpose of this report is to compare and contrast New Zealand housing trends and policies with those of United States. The report summarizes lessons learned from the United States and highlights data needs and research questions that may require further consideration in order to better understand housing markets in New Zealand.
Keywords: R31; R38; 330; Housing; Land Use Regulation; Economic Development; Immobilienpreis; Landnutzung; Wohneigentumspolitik; Wirtschaftswachstum; USA; Vergleich; Neuseeland